Design and Build API-Based Multistore Marketplace Using Agile Methodology - Fernando, Donny; Karyaningsih, Dentik (Jejaring Penelitian dan Pengabdian Masyarakat, 2024)
The business activities of a company require technology that can drive operational efficiency. Marketplaces have become one of the effective marketing channels today for promoting the company's products and services. To reach a broader market, having more than one store on a marketplace is a choice that many companies currently opt for. However, managing multiple stores on marketplaces is not an efficient management approach. This research is an applied study conducted in one startup company (profitto.co.id) that sells developing furniture components, aiming to provide the implementation of an API-based system integration solution to manage multiple stores on Tokopedia and utilizes the Scrum methodology for software development.